Reformasi Kelembagaan Mahkamah Konstitusi Dalam Menjaga Independensi Kekuasaan Kehakiman - Sulis Fauziah (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This article discusses how the independence of the judiciary is based on the Constitutional Court Decision. The obligation of a state of law or rechstaat is the independence of the judiciary. In the concept of Rule of Law and Rechstaat, a state of law is obliged to place a free and impartial judiciary against anyone. The judiciary is also called the broadest possible independence, this is meant as a sign of a good state of law. Independence is usually considered as protection from irresponsible actions. Therefore, in accordance with the mandate of Article 24 paragraph (1) of the 1945 Constitution, it is necessary to explore the roots of the independence of the judiciary. The opinion of the Constitutional Court itself regarding the decisions that make this Article a kind of test for the judicial review carried out by the Constitutional Court which should be properly discussed and raised as an interpretation of the meaning of the independence of the judiciary. This article discusses the judge's perspective on the decision of the Constitutional Court which discusses the independence of the judiciary. The writing of normative juridical uses a conceptual approach and a case approach. Secondary data is used in this article, and the main legal source is the Decision of the Constitutional Court. Data were analyzed using a qualitative approach.